2021
DOI: 10.3390/ijms222111882
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Gene Expression Plasticity in Stipa grandis in Response to Grazing Intensity Differences

Abstract: Organisms have evolved effective and distinct adaptive strategies to survive. Stipa grandis is a representative species for studying the grazing effect on typical steppe plants in the Inner Mongolia Plateau. Although phenotypic (morphological and physiological) variations in S. grandis in response to long-term grazing have been identified, the molecular mechanisms underlying adaptations and plastic responses remain largely unknown. Here, we performed a transcriptomic analysis to investigate changes in gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 107 publications
(127 reference statements)
1
7
0
Order By: Relevance
“…Even though no apparent difference was found between the PcERG3 Δ transformant KE2-1 and the wild-type strain, their transcriptomes were distinctly different, with many DEGs being identified. This suggests that the transcriptome of Phytophthora can be very plastic, as reported in other organisms ( Vesga et al, 2020 ; Dang et al, 2021 ). This plasticity may enable Phytophthora spp.…”
Section: Discussionsupporting
confidence: 59%
“…Even though no apparent difference was found between the PcERG3 Δ transformant KE2-1 and the wild-type strain, their transcriptomes were distinctly different, with many DEGs being identified. This suggests that the transcriptome of Phytophthora can be very plastic, as reported in other organisms ( Vesga et al, 2020 ; Dang et al, 2021 ). This plasticity may enable Phytophthora spp.…”
Section: Discussionsupporting
confidence: 59%
“…GAPDHase (tr|A0A446MF32) was significantly upregulated by 1.75‐fold under MG but downregulated (by approximately 0.46‐fold compared with MG) under HG. In S. grandis , coding genes of RuBisCo and GAPDHase were highly expressed under moderate and HG conditions, leading to overcompensatory growth and increased photosynthetic capacity under HG compared with MG (Dang et al, 2021). Similarly, S. breviflora showed a significant increase in the relative expression levels of RuBisCo and GAPDHase, as well as P n s, under MG.…”
Section: Discussionmentioning
confidence: 99%
“…Grazing tolerance occurs when plants modify their metabolism to aid their survival when being grazed. This may include changes to physiological and biochemical characteristics of plants such as redistribution of carbohydrates and increased photosynthetic rate, cell membrane osmoregulatory capacity, and phytohormone secretion (Benot et al, 2019; Dang et al, 2021; Zhao et al, 2021). A study assessed the physiological indicators of desert grassland forage plants in response to grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, Fterich et al (2012) demonstrated that microbial biomass of soil is maximal at low-to-intermediate levels of grazing influence and that the phenotypic evenness of the microbial community declines as the intensity of grazing increases, and soil microbial communities of heavily grazed sites are dominated by bacterial-based channels of decomposition. Lastly, a recent study of differentially expressed genes in Stipa grandis in steppe grassland in Inner Mongolia has shown that increased grazing pressure promotes expression of the Calvin-Benson cycle ( Dang et al, 2021 ). Others have also noted that herbivory has a generally positive feedback effect, and can promote plant regrowth as well as energy and nutrient flows in grazed landscapes ( Zhang Y. J. et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%